Activation of NLRP3 Inflammasome by Virus-Like Particles of Human Polyomaviruses in Macrophages - Lučiūnaitė, Asta; Dalgėdienė, Indrė; Žilionis, Rapolas; Mašalaitė, Kristina; Norkienė, Milda; Šinkūnas, Andrius; Gedvilaitė, Alma; Kučinskaitė-Kodzė, Indrė; Žvirblienė, Aurelija (Frontiers in Immunology, 2022)
Viral antigens can activate phagocytes inducing inflammation but the mechanisms are barely explored. This study aimed to investigate how viral oligomeric proteins of different structures induce inflammatory response in macrophages. Human THP-1 cell line was used to prepare macrophages which were treated with filamentous nucleocapsid-like particles (NLPs) of paramyxoviruses and spherical virus-like particles (VLPs) of human polyomaviruses. The effects of viral proteins on cell viability, pro-inflammatory cytokines’ production, and NLRP3 inflammasome activation were investigated. Filamentous NLPs did not induce inflammation while spherical VLPs mediated inflammatory response followed by NLRP3 inflammasome activation. Inhibitors of cathepsins and K+ efflux decreased IL-1β release and cell death indicating a complex inflammasome activation process. Similar activation pattern was observed in primary human macrophages. Single cell RNAseq analysis of THP-1 cells revealed several cell activation states different in inflammation-related genes. This study provides new insights into interaction of viral proteins with immune cells and suggests that structural properties of oligomeric proteins may define cell activation pathways.